Conventional bronchoscopy techniques still are as efficient as newer techniques in the diagnosis of sarcoidosis - Sehgal, Inderpaul Singh; Agarwal, Ritesh; Gupta, Dheeraj (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
N/A